Human tear peptide/protein profiling study of ocular surface diseases by SPE-MALDI-TOF mass spectrometry analyses - Nerea González (EuPA Open Proteomics, 2014)
The goal of this study was to investigate differences in tear peptidome/proteome profiles of aqueous-deficient dry eye, Meibomian gland dysfunction and control individuals. Tears from 93 individuals were collected by capillary and subjected to solid-phase extraction followed by MALDI-TOF for profiling analysis. Obtained spectra were aligned by variable penalty dynamic time warping (VPdtw) and the resulting data analyzed using multivariate statistics. Comparative analyses revealed good performance of VPdtw and a high discrimination of groups with a correct assignment of 89.3% using twelve informative peaks. SDS–PAGE followed by MALDI-TOF/TOF analysis allowed identification of lipocalin-1 as a biomarker candidate.